0115 A Pilot Study To Measure The Stress Response To The Neonatal Life Support Airway Test Amongst Different Health Care Professionals. (1st November 2014) - Holme, Nicola; Harrison, Catherine; Shaw, Ben
Abstract : Background: Resuscitation courses for healthcare professionals ensure accountability but the assessment process often considered too stressful by candidates. The neonatal life support (NLS) course involves an assessment of simple airway manoeuvres using a low fidelity manikin. The aims of the study were to: Determine whether there is variation in stress responses to the NLS airway test (NLSAT) amongst different professionals (nurses, midwives and doctors). Compare levels of experience with the stress response measured in each participant. Identify whether high stress levels correlate with difficulty passing the NLSAT. Methodology: Eighty health care professionals attending the NLS course participated. Healthcare professionals provided salivary cortisol samples and completed an anxiety questionnaire (STAI) at a baseline point and then immediately before and ten minutes after the completion of the NLSAT. Participants' demographic details and outcome from the NLSAT were recorded. Results: Cortisol measurements failed to detect any significant rise in stress levels. Significant stress levels were induced by the NLSAT when measuring STAI scores amongst all professionals (p < 0.05). STAI scores significantly rose amongst individual professional groups (p < 0.01) for midwives, nurses and doctors). Greatest changes in STAI scores were detected for midwives. Significance was not achieved when analysing impact of experience on stress levels. It was not possible to determine if stress levels impacted on performance due to the low re-sit rate (7.5%). Conclusions/recommendations: Stress levels induced by the NLSAT are significant and need to be considered when instructing, mentoring and improving the NLS course. This study has made steps towards understanding stress induced on the neonatal life support course (NLS) and how it varies amongst participating professionals. It is suggested that doctors have the lowest stress levels due to their familiarity with simulation. Consideration of booster sessions during the re-validation period is required. 1 These findings have implications for other resuscitation/simulation courses. Reference: Mosley C, Dewhurst C, Molloy S, Shaw BN. What is the impact of structured resuscitation training on healthcare practitioners, their clients and the wider service? A BEME systematic review: BEME Guide No 20. Med Teach 2012;34(6):e349–85